STRATEGI PENINGKATAN DAYA SAING MADRASAH DI ERA DIGITAL - Handayani; Sirozi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the strategy of increasing the competitiveness of Madrasah in the digital era. The method of writing this article uses literature study or literature research. Manage and analyze reference sources from articles, journals, and other sources from the internet. The results of this study show that the implementation or application of strategies to increase the competitiveness of madrasas in the digital era through branding image by forming superior programs, increasing achievements, and shaping the character of akhlakul karimah will make madrasas have a positive image in the surrounding environment, and can build progress for madrasas in the future, including in the era of society 5.0, and with the branding strategy image of madrasas managed to get a positive image from the community, the institution can also maintain its quality and quality can generate full trust from the community.